Factors Influencing Maritime Vocational Students’ Difficulties in Translating English Vocabulary: A Case Study at SMK Pelayaran Lintas Nusantara Barru - Syamsinar Syamsinar; Murni Mahmud; Maemuna Muhayyang (Faculty of Education and Teacher Training of UIN Palopo, 2025)
Vocabulary translation ability is a crucial component of English language learning, particularly for students in vocational schools preparing for international professional fields such as maritime studies. However, many students still encounter various challenges in translating both general and technical vocabulary. This study aims to analyze the factors associated with students’ difficulties in translating vocabulary at SMK Pelayaran Lintas Nusantara Barru and to identify the most dominant factors influencing these difficulties. This research employed a quantitative descriptive approach involving 60 students from grades X, XI, and XII of SMK Pelayaran Lintas Nusantara Barru. Data were collected through questionnaires and semi-structured interviews, then analyzed using descriptive statistics and Pearson correlation tests. The study examined internal factors (language ability, motivation, interest, and learning strategies) and external factors (teaching methods, learning media, and learning environment). The findings revealed that students' difficulty with vocabulary translation was high, with an average score of 3.67. Both internal and external factors showed a positive and significant correlation with students’ translation difficulties, with language ability (r = 0.68) and learning strategies (r = 0.63) being the most important contributors.Meanwhile, the learning environment showed the weakest relationship (r = 0.38). These results indicate that students' translation difficulties are primarily influenced by limited language proficiency and ineffective learning strategies. Therefore, it is recommended that teachers adopt more contextual teaching methods and utilize interactive learning media to enhance students' comprehension and practical application of vocabulary.